Displacements of an Active Moderately Rapid Landslide—A Dataset Retrieved by Continuous GNSS Arrays - Marco Mulas; Giuseppe Ciccarese; Giovanni Truffelli; Alessandro Corsini (Data, 2020)
This paper describes a dataset of continuous GNSS positioning solutions referring to slope movements in the Ca’ Lita landslide (Northern Apennines, Italy). The dataset covers the period from 24 March 2016 to 17 July 2019 and includes time-series of the daily position of three GNSS rovers located in different parts of the landslide: head zone, upper track zone, and lower track zone. Two different types of continuous GNSS arrays have been used: one is based on high-end Leica geodetic receivers, and the other is based on low-cost effective Emlid receivers. Displacements captured in the dataset are up to more than a hundred meters and are characterized by prolonged phases of slow movement and moderately rapid acceleration phases. The data presented in this contribution were used to underline slope processes and validate displacements retrieved by the application of digital image correlation to a stack of a satellite images.